Computational Delays - Deshmukh, S. D. (Management Science, 1974)
Decision-making processes usually involve time-consuming and costly operations of observation and communication of the state of the environment and generation and implementation of appropriate actions. Collectively these activities may be called computational and the procedure required to carry them out may be called an algorithm. If the environment is changing stochastically the fixed computational delay involved in operating the algorithm yields obsolete actions resulting in reduced expected return. The loss as a function of delay is a measure of efficiency of the algorithm which depends upon the stochastic properties of the environment. If it is possible to reduce the loss by employing a faster algorithm at a higher cost, the algorithm may be optimally designed and selected from a given family.